PENGARUH BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA DENGAN KNOWLEDGE SHARING SEBAGAI VARIABEL MEDIASI (Studi Pada Pegawai Kantor Balai Kota Banda Aceh) - M. Subki, Afrida (Departemen Manajemen, 2016)
This study examined the Influence of Organizational Culture on Job Satisfaction With Knowledge Sharing as Mediation Variables (Study on Employee’s Central Office of Banda Aceh). The data was collected On the Employee’s Central Office of Banda Aceh. A total of 114 respondents were included. Analytical methods of this research is Hierachial Linear Modeling (HLM) and used as a method of analysis to determine the effect of the variables involved. The results showed: 1) Cultural organizations significant effect to job satisfaction in employee’s Central Office on Banda Aceh. 2) Cultural organizations significant effect to knowledge sharing on employee’s Central Office in Banda Aceh. 3) Knowledge sharing significant effect to job satisfaction on employee’s Central Office in Banda Aceh. 4) Knowledge sharing mediating the influence of organizational culture to job satisfaction on employee’s Central Office in Banda Aceh.Keywords: Organizational Culture, Job Satisfaction, Knowledge Sharing